MODEL PEMBELAJARAN BRAIN WRITING TERHADAP KEMAMPUAN MENULIS TEKS EKSPLANASI SISWA KELAS XI - Melda Bonita Br Tarigan; Inayah Hanum (Jurnal Bastra (Bahasa dan Sastra), 2025)
The aim of the research is to describe the influence of the Brain writing learning model on the ability to write explanatory text in Class Using an experimental method with a one group pre-test post-test design. Data collection techniques include observation, interviews and tests. Data analysis techniques use analysis requirements tests, normality tests, homogeneity tests, and hypothesis tests. The research results found that the average pretest score was 65, which was in the poor category, while the average posttest class score was 86, which was in the very good category. So it can be concluded that the use of the Brain writing learning model has a significant effect on the ability to write explanatory text for class XI IPA-3 SMA Swasta Masehi GBKP. This increase can be proven from the hypothesis test tcount > ttable, namely 7.22 > 1.71 which proves that there is a significant influence from the use of the Brain writing learning model on the ability to write explanatory text for class XI students of GBKP Berastagi Private High School T.A 2021/2022.